PRODUKTIVITAS KEBUN KELAPA SAWIT DENGAN APLIKASI BERBAGAI KOMBINASI PUPUK DAN JANJANG KOSONG PADA LAHAN PASIRAN - Candra Ginting; Dino Prasetio (Program Studi Agroteknologi INSTIPER, 2019)
The main problem of sandy soils is low water holding capacity, resulting an occurance of water deficit. To overcome the problem, application of empty fruit bunch (EFB) is important. EFB application increases growth and development of fruit set and productivity, which causes an increase of palm oil absorbing ability to nutrients. Therefore, increasing potential effectivity of fertilizer in sandy soil is needed. Applying of EFB 79 to 268 kg.plant-1 .year-1 combine with inorganic fertilizer 2.8 to 6.0 kg.plant-1 .year-1 increased productivity simultaneously in years. Results showed that fertilizer application was more effective when applied under the heap of EFB, particularly in sandy soils. Keyword: empty fruit bunch, sandy soils, productivity, fruit set, inorganic fertilizer.